Parameters of oculomotor activity and cerebral hemodynamics in students with different types of autonomic reactivity while performing cognitive tasks - Anna I. Taleeva; Natalya V. Zvyagina; Olga E. Karyakina; Nikolay V. Popov; Tatyana V. Zotikova (Digital Diagnostics)
BACKGROUND: At the current state of human development, with the high rates of knowledge accumulation and accelerated social and technical evolution, studying the psychophysiological features of cognitive activity within a limited time is essential.